The Mechanisms and Animal Models of SARS-CoV-2 Infection - Jia, Wenrui; Wang, Juan; Sun, Bao; Zhou, Jiecan; Shi, Yamin; Zhou, Zheng (Frontiers in Cell and Developmental Biology, 2021)
Coronavirus disease 2019 (COVID-19) is a highly contagious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has aroused great public health concern worldwide. Currently, COVID-19 epidemic is spreading in many countries and regions around the world. However, the study of SARS-CoV-2 is still in its infancy, and there is no specific therapeutics. Here, we summarize the genomic characteristics of SARS-CoV-2. In addition, we focus on the mechanisms of SARS-CoV-2 infection, including the roles of angiotensin converting enzyme II (ACE2) in cell entry, COVID-19 susceptibility and COVID-19 symptoms, as well as immunopathology such as antibody responses, lymphocyte dysregulation, and cytokine storm. Finally, we introduce the research progress of animal models of COVID-19, aiming at a better understanding of the pathogenesis of COVID-19 and providing new ideas for the treatment of this contagious disease.